Analisis Tingkat Kepuasan Mahasiswa dalam Pengisian KRS di Website Student Universitas Amikom Purwokerto Menggunakan Metode EUCS - Priyanti, Dika; Fadhila Intan Cahyaningrum; Dimas Sigit Purnomo; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Student Web is an information system developed by Amikom University Purwokerto to assist students in managing academic administration, including filling out Study Plan Cards (KRS). However, this website often experiences disruptions and errors during KRS filling periods with high access, resulting in difficulties in accessing, delays in course selection, and schedule conflicts. This has an impact on student satisfaction in using the service. This research aims to measure the level of user satisfaction with the quality of the Amikom University Purwokerto Student Website on the KRS filling feature, using the End User Computing Satisfaction (EUCS) method. The sample consisted of 100 active students at Amikom University, Purwokerto. The results of the hypothesis test show that there is 1 variable that does not show a significant influence, namely the content variable, and there are 4 variables that have an influence, namely accuracy, format, ease of use and timeliness.